Demand Research of Airport Chairs Based on Kano/Function Behavior Structure Model - Qianwei Liang; Yushu Chen (BioResources, 2024)
To improve the use experience of airport chairs, this study adopted morphological analysis to conduct systematic deconstruction, analysis, and statistics on the modeling features of existing airport chairs. The KJ method was used to determine the design requirements of airport chairs. The study combined the Kano model to classify the functional attributes and prioritize the requirements, and it merged the module and demand analysis to build a Function-Behavior-Structure mapping model. In this way, passengers’ demand for airport chairs can be clearly defined, and airport chair configuration planning can be carried out according to the difference in preferences. Further, different module combination schemes can be formed to improve the functional allocation efficiency of airport chairs, optimize the overall service quality of airports, and provide some basis and reference for the future design of airport chairs.